EFEKTIVITAS MODEL PEMBELAJARAN SEARCH, SOLVE, CREATE AND SHARE TERHADAP KEMAMPUAN CREATIVE PROBLEM SOLVING PESERTA DIDIK SMP PADA PEMBELAJARAN IPA MATERI SUHU DAN KALOR - Nurul Khairunnisa; Nur Islami; Muhammad Sahal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Creative problem solving ability is a process, method, or system for approaching problems imaginatively and producing effective actions. The ability to suppress various alternative ideas and ideas to seek various possible actions at each step of the problem solving process. This study aims to determine the effectiveness of the Search, Solve, Create, and share learning model, its impact on students' creative problem solving abilities. The research was conducted on class VII students of SMP Negeri 1 Kubu on temperature and heat. The classes taken were class VII.1 with a total of 22 students and class VII.2 with a total of 22 students where the two classes consisted of an experimental class and a control class. The data collection instrument was a test on the results of the ability to solve creative problem solving on class VII heat and temperature material which consisted of 12 objective questions. This type of research is a quasi-experimental design with a Posttest Only Non-equivalent Control Group Design. The independent sample t-test with the help of SPSS version 23 shows that the Search, Solve, Create and Share model has an effect on students' creative problem solving abilities. The creative problem solving abilities of the experimental class students were better than the control class. Furthermore, the average value of the experimental class was 67.77 and that of the control class was 56.03. These results indicate that the Search, Solve, Create and Share learning model is effective on students' creative problem solving abilities, with the good category.Keyword: Model Search, Solve, Create and Share, Creative Problem Solving Abilities, Temperature and Heat.